Signifikante Verbesserungen eines klinischen Untersuchungskurses nach einfachen strukturierten Veränderungen des Lehrinhalts und der Lehrmethoden [Significant improvement of a clinical training course in physical examination after basic structural changes in the teaching content and methods] - Bott-Flügel, Lorenz (GMS Zeitschrift für Medizinische Ausbildung, 2013)
[english] Background: Regular student evaluations at the Technical University Munich indicate the necessity for improvement of the clinical examination course. The aim of this study was to examine if targeted measures to restructure and improve a clinical examination course session lead to a higher level of student satisfaction as well as better self-assessment of the acquired techniques of clinical examination.Methods: At three medical departments of the Technical University Munich during the 2010 summer semester, the quantitative results of 49 student evaluations (ratings 1-6, German scholastic grading system) of the clinical examination course were compared for a course before and a course after structured measures for improvement. These measures included structured teaching instructions, handouts and additional material from the Internet.Results: 47 evaluations were completed before and 34 evaluations after the measures for improvement. The measures named above led to a significant improvement of the evaluative ratings in the following areas: short introduction to the topic of each clinical examination course (from 2.4±1.2 to1.7±1.0; p=0.0020) and to basic measures of hygiene (from 3.8±1.9 to 2.5±1.8; p=0.004), structured demonstration of each clinical examination step (from 2.9±1.5 to 1.8±1.0; p=0.001), sufficient practice of each clinical examination step (from 3.1±1.8 to 2.2±1.4; p=0.030) structured feedback on each clinical examination step (from 3.0±1.4 to 2.3±1.0; p=0.0070), use of handouts (from 5.2±1.4 to 1.8±1.4; p<0.001), advice on additional learning material (from 5.0±1.4 to 3.4±2.0; p<0.001), general learning experience (from 2.4±0.9 to 1.9±0.8; p=0.017), and self-assessment of the acquired techniques of clinical examination (from 3.5±1.3 to 2.5±1.1; p<0.01).Conclusion: Structured changes led to significant improvement in the evaluative ratings of a clinical examination course session concerning preparation of the tutors, structure of the course, and confidence in performing physical examinations. [german] Hintergrund: Die regelmäßigen Evaluationen der Studierenden der Technischen Universität München deuten auf einen Verbesserungsbedarf des klinischen Untersuchungskurses hin. Ziel der vorliegenden Studie war es, zu prüfen, ob gezielte Maßnahmen zur Umstrukturierung und Verbesserung eines Untersuchungskurstages zu einer höheren Zufriedenheit der Studierenden und zu einer besseren Selbsteinschätzung der von ihnen erlernten Untersuchungstechniken führen.Methoden: In drei medizinischen Kliniken der Technischen Universität München wurden im Sommersemester 2010 die quantitativen Evaluationsergebnisse (deutsches Schulnotensystem, Noten 1-6) von insgesamt 49 Studierenden von einem Kurstag vor und einem Kurstag nach strukturierten Verbesserungsmaßnahmen des klinischen Untersuchungskurses verglichen. Zum Einsatz kamen strukturierte Instruktion der Dozenten, Handouts und über das Internet verfügbares Zusatzmaterial.Ergebnisse: Es wurden 47 Evaluationsbögen vor und 34 Evaluationsbögen nach den Verbesserungsmaßnahmen ausgefüllt. Die oben genannten Maßnahmen führten zu signifikanten Verbesserungen der Evaluationsnoten in folgenden Bereichen: Einführen ins jeweilige Kursthema (von 2,4±1,2 auf 1,7±1,0, p=0,002) und in hygienische Maßnahmen (von 3,8±1,9 auf 2,5±1,8, p=0,004), strukturiertes Vorführen der einzelnen Untersuchungsschritte (von 2,9±1,5 auf 1,8±1, p=0,001), Üben der Untersuchungsschritte (von 3,1±1,8 auf 2,2±1,4, p=0,030), strukturiertes Feedback zur Untersuchungstechnik (von 3,0±1,4 auf 2,3±1,0, p0,=0,007), Verwenden von Handouts (von 5,2±1,4 auf 1,8±1,4, p<0,001), Tipps zu weiterem Lernmaterial (von 5,0±1,4 auf 3,4±2,0, p<0,001), Lernerfahrung insgesamt (von 2,4±0,9 auf 1,9±0,8, p=0,017) und Selbsteinschätzung der Studenten bezüglich der Sicherheit bei der Durchführung einer körperlichen Untersuchung (von 3,5±1,3 auf 2,5±1,1, p<0,001).Zusammenfassung: Strukturierte Verbesserungsmaßnahmen führten zu signifikanten Verbesserungen der Evaluationsnoten eines klinischen Untersuchungskurstages in den Bereichen „Vorbereitung der Dozenten“, „Struktur des Kurses“ und „selbst eingeschätzte Sicherheit beim Durchführen einer Untersuchung“.